110k views
4 votes
Which expressions are equivalent to -3(2w+6)-4

User Harthoo
by
5.1k points

2 Answers

3 votes

Answer:

B is the answer

Step-by-step explanation:

-3(2w+6)-4

-6w-18-4

-6w-22

User Renato Aquino
by
5.2k points
4 votes

Answer:

B = 2(−3w + (−11)) is the answer.

Step-by-step explanation:

-3(2w + 6) - 4

1. Distribute

= -3*2w = -6w

= -3 * 6 = -18

= -6w -18

2. Simplify like terms

= -18 - 4

= -22

3. Place variables and numbers together

= -6w - 22

-6w -22 is the answer.

So, B is the answer.

Step-by-step explanation:

2 * -3w = -6w

2*-11 = -22

Place them together and you get the answer!

User Gareth Simpson
by
4.7k points